Colloquial Spanish the complete course for beginners - Alday, Untza Otaola; Routledge (Firm) (Boca Raton, FL: Routledge, 2010)
Learn Spanish language more easy. This CD is complete course for the beginner
Title from container
English and Spanish
Keywords: Spanish language -- Spoken Spanish; Japanese language -- Study and teaching; Japanese language -- Study and teaching -- Foreign speakers; Spanish language -- Self-instruction